2022
DOI: 10.3390/nu14102087
|View full text |Cite
|
Sign up to set email alerts
|

An Overview of Obesity, Cholesterol, and Systemic Inflammation in Preeclampsia

Abstract: Preeclampsia (PE), an inflammatory state during pregnancy, is a significant cause of maternal and fetal morbidity and mortality. Adverse outcomes associated with PE include hypertension, proteinuria, uterine/placental abnormalities, fetal growth restriction, and pre-term birth. Women with obesity have an increased risk of developing PE likely due to impaired placental development from altered metabolic homeostasis. Inflammatory cytokines from maternal adipose tissue and circulating cholesterol have been linked… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
7

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 53 publications
0
20
0
7
Order By: Relevance
“…The correlation heat map further confirmed that cholesterol was negatively correlated with acetic acid and propionic acid levels. Another study found that increased adipose tissue and cholesterol in pregnant women promoted metabolic abnormalities and systemic inflammation, leading to poor placental vascularization and promoting the occurrence of PE ( Alston et al., 2022 ). The reason for this difference may be related to dyslipidemia of pregnancy (DLP) caused by insulin resistance, increased lipoprotein synthesis, and lipolysis during normal pregnancy in the NP group ( Gao et al., 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…The correlation heat map further confirmed that cholesterol was negatively correlated with acetic acid and propionic acid levels. Another study found that increased adipose tissue and cholesterol in pregnant women promoted metabolic abnormalities and systemic inflammation, leading to poor placental vascularization and promoting the occurrence of PE ( Alston et al., 2022 ). The reason for this difference may be related to dyslipidemia of pregnancy (DLP) caused by insulin resistance, increased lipoprotein synthesis, and lipolysis during normal pregnancy in the NP group ( Gao et al., 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Ожиріння пов'язане з підвищеним ризиком ряду серйозних несприятливих наслідків. За сучасними даними, ускладнення ґестаційного процесу у жінок з ожирінням відзначаються у 45-85% випадків [8]. MBRRACE 2015 виявив, що більше половини жінок, які померли прямо чи опосередковано від причин, пов'язаних з вагітністю, мали надлишкову вагу або ожиріння [21].…”
Section: метаболічні аспекти розвитку прееклампсіїunclassified
“…Біосинтез клітинного холестерину та гомеостаз холестерину підтримується переважно печінкою, але холестерин також зберігається в жировій тканині [18]. Останні дослідження показують, що жирова тканина служить основним місцем зберігання вільного холестерину, а збільшення накопичення холестерину паралельно з ожирінням [8,18]. При ожирінні приблизно 50% холестерину в організмі зберігається в жировій тканині.…”
Section: результати та їх обговоренняunclassified
See 1 more Smart Citation
“…It has been suggested that chronic low-level inflammation is one of the most important causes of insulin resistance onset, since chronic exposure to pro-inflammatory cytokines can impair insulin signaling pathways and decrease insulin secretion from beta cells [ 5 ]. Inflammation is the result of cellular damage and characterizes many pathologies, including cancer [ 11 , 12 , 13 ] and immune diseases [ 14 ], but also pregnancy complications, such as preeclampsia and preterm birth [ 15 , 16 , 17 , 18 ]. Chronic low-grade inflammation is a pathological condition, playing an important role in the pathogenesis and progression of some pathologies, including GDM, metabolic syndrome, DM and cardiovascular diseases [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%